Detrimental Effect of C-Reactive Protein on the Cardiometabolic Cells and Its Rectifying by Metabolic Surgery in Obese Diabetic Patients - Sun F (Dove Medical Press, 2020)
Fang Sun,1,* Zhigang Zhao,1,* Qiang Li,1 Xunmei Zhou,1 Yingsha Li,1 Hexuan Zhang,1 Zhencheng Yan,1 Hongbo He,1 Zhigang Ke,2 Yu Gao,2 Fan Li,2 Weidong Tong,2 Zhiming Zhu1 1Department of Hypertension and Endocrinology, Daping Hospital, Third Military Medical University, Center for Hypertension and Metabolic Diseases, Chongqing Institute of Hypertension, Chongqing 400042, People’s Republic of China; 2Department of General Surgery, Daping Hospital, Third Military Medical University, Chongqing 400042, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiming Zhu Tel +86-23-6876-7849Fax +86-23-6870-5094Email zhuzm@yahoo.comBackground: High-sensitivity C-reactive protein (hs-CRP) has been regarded as a biomarker of low-degree inflammation in illness; however, whether CRP exerts its pathogenic effect on the cardiometabolic system remains unknown. Aside from the beneficial effects of metabolic surgery on cardiometabolic system, its impact on inflammation still worth examining. Thus, this study aims to investigate the effect of CRP on adipose and vascular cells, and their responses to metabolic surgery in obese diabetic patients.Patients and Methods: The expression of CRP and RAS- and ERK-related factors in the adipocytes and VSMCs were measured. Obese patients with type 2 diabetes who underwent metabolic surgery were followed up for 2 years thereafter. Laboratory tests, which included serum hs-CRP levels and visceral fat thickness (VFT), were obtained before and after surgery.Results: CRP administration significantly and dose-dependently increased the intracellular-free calcium concentration ([Ca2+]i) in cultured adipocytes and in the VSMCs. CRP administration significantly increased ACE, Ang II, AT1R and p-ERK expressions, but reduced ACE2 expression in both the adipocytes and VSMCs. Clinical study showed that VFT was closely associated with serum hs-CRP. Furthermore, VFT and serum hs-CRP were found to be highly associated with blood pressure. Finally, metabolic surgery remarkably decreased blood pressure, visceral fat and serum hs-CRP levels.Conclusion: CRP has a detrimental effect on cardiometabolic cells, aside from functioning merely as a biomarker. Serum hs-CRP levels are highly associated with hypertension and visceral obesity, which can be antagonized by metabolic surgery in obese diabetic patients.Keywords: CRP, metabolic surgery, type 2 diabetes